Sex-Specific Patterns in Abundance, Temporary Emigration and Survival of Indo-Pacific Bottlenose Dolphins (Tursiops aduncus) in Coastal and Estuarine Waters - Sprogis, Kate R.; Pollock, Kenneth H.; Raudino, Holly C.; Allen, Simon J.; Kopps, Anna M.; Manlik, Oliver; Tyne, Julian A.; Bejder, Lars (Frontiers in Marine Science, 2016)
Inherent difficulties in determining the sex of free-ranging sexually monomorphic species often prevents a sex-specific focus on estimating abundance, movement patterns and survival rates. This study provides insights into sex-specific population parameters of Indo-Pacific bottlenose dolphins (Tursiops aduncus). Systematic, boat-based photo-identification surveys (n = 417) were conducted year-round from 2007-2013 in coastal and estuarine waters off Bunbury, Western Australia. Pollock’s Robust Design was used to quantify population parameters for three datasets: i) adults and juveniles combined, ii) adult females and iii) adult males. For all datasets, abundance estimates varied seasonally, with general highs during summer and/or autumn, and lows during winter. Dolphins had seasonally structured temporary emigration rates with similar trends between sexes. The derived return rate (1-γ’) of temporary emigrants into the study area was highest from winter to spring, indicating that dolphins had a high probability of return into the study area during spring. We suggest that the return of dolphins into the study area and increase in abundance is influenced by the breeding season (summer/autumn). Prey availability is likely a main driver responsible for the movement of dolphins out of the study area during winter. Seasonal apparent survival rates were constant and high (0.98-0.99) for all datasets. High apparent survival rates suggest there is no permanent emigration from the study area. Our sex-specific modeling approach offers a comprehensive interpretation of the population dynamics of a top predator in a coastal and estuarine environment and acts as a model for future sex-based population studies on sexually monomorphic species.